The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1034/j.1600-0609.2003.00079.x
|View full text |Cite
|
Sign up to set email alerts
|

The presence of a significant association between elevated PRV‐1 mRNA expression and low plasma erythropoietin concentration in essential thrombocythaemia

Abstract: Approximately 45% of newly diagnosed patients with essential thrombocythaemia (ET) demonstrate subnormal plasma erythropoietin (EPO) concentrations, which constitutes a risk factor for occlusive vascular events. In 58 ET patients, a possible association between polycythaemia rubra vera-1 (PRV-1) overexpression and subnormal plasma EPO was investigated, which was always measured prior to the institution of platelet lowering agents. At the time when PRV-1 expression was measured, 28 of 58 (48%) ET patients had r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 18 publications
0
18
1
1
Order By: Relevance
“…PRV1 is a hematopoietic cell surface receptor that has been shown to transduce intracellular signals leading to proliferation, involving JAK2 and Src kinases [16]. PRV1 is overexpressed in MPN patients [15,19,41,42] and seems to be associated with PV disease phenotype characterized by high erythrocyte and low platelet counts [15]. These studies also described a correlation between PRV1 expression and the JAK2 V617F allele burden, as well as between PRV1 overexpression and elevated JAK2 tyrosine kinase activity [15,19,25,41,42].…”
Section: Discussionmentioning
confidence: 99%
“…PRV1 is a hematopoietic cell surface receptor that has been shown to transduce intracellular signals leading to proliferation, involving JAK2 and Src kinases [16]. PRV1 is overexpressed in MPN patients [15,19,41,42] and seems to be associated with PV disease phenotype characterized by high erythrocyte and low platelet counts [15]. These studies also described a correlation between PRV1 expression and the JAK2 V617F allele burden, as well as between PRV1 overexpression and elevated JAK2 tyrosine kinase activity [15,19,25,41,42].…”
Section: Discussionmentioning
confidence: 99%
“…Considering the values for sensitivity and specificity reported in Table II, it can be concluded that the current conventional tests are, at least, equally useful (Messinezy et al , 2002; Zwicky et al , 2002). It remains to be established whether evaluation of neutrophil CD177 mRNA may be employed for defining prognosis (Johansson et al , 2003) or monitoring disease activity in the individual patient with CMD.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in a considerable number of patients with ET a significant association between a low erythropoietin level and an elevated PVR-1 gene expression was described [36]. Although the occurrence of this concurrent marker profile was recognized to a far lesser degree in other series [37, 38], it has been suggested that two types of ET may be distinguished [35, 39] and that PVR-1-positive ET reveals a higher risk for vascular complications [40].…”
Section: Discussionmentioning
confidence: 99%